2016
DOI: 10.18632/oncotarget.10286
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics profiles delineate uridine deficiency contributes to mitochondria-mediated apoptosis induced by celastrol in human acute promyelocytic leukemia cells

Abstract: Celastrol, extracted from “Thunder of God Vine”, is a promising anti-cancer natural product. However, its effect on acute promyelocytic leukemia (APL) and underlying molecular mechanism are poorly understood. The purpose of this study was to explore its effect on APL and underlying mechanism based on metabolomics. Firstly, multiple assays indicated that celastrol could induce apoptosis of APL cells via p53-activated mitochondrial pathway. Secondly, unbiased metabolomics revealed that uridine was the most notab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…However, HL-60 can respond to ATRA 22 , which is widely used as a cell line in the APL studies [24][25][26][27] . In our previous study 28 , consistent to previous reports 15,[19][20][21] , we also found celastrol caused apoptosis in HL-60 cells, indicating the key role of apoptosis in the effect of celastol in the treatment of acute leukemia.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…However, HL-60 can respond to ATRA 22 , which is widely used as a cell line in the APL studies [24][25][26][27] . In our previous study 28 , consistent to previous reports 15,[19][20][21] , we also found celastrol caused apoptosis in HL-60 cells, indicating the key role of apoptosis in the effect of celastol in the treatment of acute leukemia.…”
supporting
confidence: 92%
“…Surveying these small molecules provides an overall understanding of biological mechanisms, thereby creating a more complete picture of the phenotype (the observable characteristics of a living system). In our previous study, we used metabolomics to study the underlying mechanism in HL-60 cells in vitro, and identified uridine was the most notable changed metabolite after celastrol treatment 28 . However, the metabolome changes in vivo are unknown.…”
mentioning
confidence: 99%
“…To maintain homeostasis of HOS cells, a large number of unfolded proteins activate the PERK signaling pathway by binding to Bip, and PERK, which is an important transducer, activates downstream molecular partners and protein secretion related to molecular gene transcription. To explore whether attenuating the expression of PERK signaling pathway members would reverse the protective effect of ERS induced by celastrol and further promote the apoptosis of HOS cells, we used an inhibitor of PERK (GSK2656157, 5 mM) to pretreat HOS cells for 1 h before celastrol treatment (19,20). Following treatment with GSK2656157, the proliferation of HOS cells was further inhibited compared with that of the celastrol group; karyopyknosis, condensation, karyorrhexis and other typical apoptotic bodies were more evident; and the apoptosis rates further increased, while immunofluorescence revealed that the expression of p-PERK was significantly attenuated (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, numerous studies have revealed that many components extracted from traditional Chinese medicine have antitumor effects (3,8,10). Celastrol, extracted from the root of T. wilfordii, has been revealed to inhibit the proliferation of tumors, and the mitochondrial apoptotic pathway and death receptor apoptosis pathway were involved in the celastrol-induced apoptosis (19,20). Research has reported the effect of celastrol on osteosarcoma, which has demonstrated great antitumor potential.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomics can be used to evaluate hepatotoxicity [ 47 ], cerebral lesion [ 48 ], and nephrotoxicity [ 49 ], and evaluate the safety of natural products, such as noscapine and Butea monosperma extract (Table 1 ) [ 50 , 51 ]. Using the powerful technology, the toxicity and safety of various natural products have been evaluated, such as noscapine [ 50 ], bupleurotoxin [ 48 ], celastrol [ 52 ], TP [ 5 ], and various extracts of natural products (Table 1 and Fig. 8 ).…”
Section: Metabolomics Explores the Toxicity Of Natural Productsmentioning
confidence: 99%